MENABI PAGE DALAM BENTUK AUDIO VISUAL BERBASIS WEB BAGI SISWA KELAS X SEKOLAH MENENGAH ATAS KABUPATEN PAKPAK BHARAT - Erlupiana Solin; Sitti Rahmah (Universitas Negeri Medan, 2020)
ABSTRACTThe Aimed of this research was to describe how the packaging of the Tatak Menabi Page through web-based audio-visual media for The 10th Grade of Senior High School Students in Pakpak Bharat Regency. The theory used in this research are Julianti's theory which states that packaging is the manufacture, packaging of goods or packaging products that aim to protect the goods which are supported by several components according to the needs of product packaging and the theory of Haryono which states that there are 3 stages of packaging audiovisual media web-based, namely 1. Stage of Design Making, 2. Production Phase. 3. Trial Phase. The Data collection techniques were carried out by doing observation, interviews, documentation and literature studies which were conducted to observe the needs of the media, record the results of interviews and document the form of videos and photos used in making audio-visual media. These data were then analyzed with qualitative descriptive methods and laboratory work. In Packaging Tatak Menabi Page, a validation test of material experts and media experts were carried out. The results of the material expert validation test for the Tatak Menabi Page material got score 4.55 and for the validation test of the Tatak Menabi Page from the media experts got score 4.58. It can be concluded that the Tatak Menabi Page packaging product in the form of web-based audio visual media was declared suitable for being used as teaching material for learning in schools. Keywords: Packaging, Audio Visual Media, Web Media, Tatak Menabi Page